2017
DOI: 10.1371/journal.pcbi.1005843
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study of budding yeast colony formation and its relationship to budding pattern and aging

Abstract: Budding yeast, which undergoes polarized growth during budding and mating, has been a useful model system to study cell polarization. Bud sites are selected differently in haploid and diploid yeast cells: haploid cells bud in an axial manner, while diploid cells bud in a bipolar manner. While previous studies have been focused on the molecular details of the bud site selection and polarity establishment, not much is known about how different budding patterns give rise to different functions at the population l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Developing a modeling framework for investigating prion disease dynamics within an entire yeast colony is challenging because it requires capturing the physical processes on an individual cell level that determine colony growth (i.e., budding and variable cell cycle length) as well as capturing the interplay of individual cell processes with protein aggregation dynamics (i.e., asymmetric protein distribution at the time of division, persistence of diseased phenotype/aggregate that was given to daughter while it grows to begin a new cell cycle, lineage-dependent protein propagation). Several models have already been developed to investigate physical mechanisms controlling patterns of yeast colony growth such as cell division polarity, mother-daughter size asymmetry, and cell-cell adhesion via budding of the new daughter cell [92,93,105]. Jönsson and Levchenko developed an offlattice, center-based model in which cells are modeled as elastic spheres of variable size [92].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Developing a modeling framework for investigating prion disease dynamics within an entire yeast colony is challenging because it requires capturing the physical processes on an individual cell level that determine colony growth (i.e., budding and variable cell cycle length) as well as capturing the interplay of individual cell processes with protein aggregation dynamics (i.e., asymmetric protein distribution at the time of division, persistence of diseased phenotype/aggregate that was given to daughter while it grows to begin a new cell cycle, lineage-dependent protein propagation). Several models have already been developed to investigate physical mechanisms controlling patterns of yeast colony growth such as cell division polarity, mother-daughter size asymmetry, and cell-cell adhesion via budding of the new daughter cell [92,93,105]. Jönsson and Levchenko developed an offlattice, center-based model in which cells are modeled as elastic spheres of variable size [92].…”
Section: Discussionmentioning
confidence: 99%
“…Their work showed that cell growth inhibition by neighboring cells and polar division growth patterns were the most significant factors driving appreciable differences in the shape and size of yeast colony development. In addition, Wang et al built an off-lattice, center-based model that incorporates key biological processes in yeast cell colonies including budding, mating, mating type switch, changes in cell cycle length and cell size due to aging, and cell death [93]. The main results of their work include proposed mechanisms for how budding patterns in yeast cells affect colony growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bud1p/Rsr1p, a Rho-GTPase family protein, is a core component of the cell polarity machinery that is essential for polarized bud site selection in yeast. Polarized bud site selection may promote colony expansion in diploid yeast or mating in haploid yeast (Wang et al, 2017).…”
Section: Role For the Polarity Machinery In Lifespan Control In Yeastmentioning
confidence: 99%